Pengembangan Ekowisata Berbasis Ekonomi Peluang Bisnis di Era Revolusi Industri 4.0 Desa Patuanan Kecamatan Leuwimunding Kabupaten Majalengka - Toto Sukarnoto (Etos : Jurnal Pengabdian Masyarakat, 2020)
A strong and sustainable regional economic development is an effective collaboration between the use of existing resources, the community and the government. One of the optimal resource utilization efforts is to develop tourism with the concept of Ecotourism. The industrial revolution 4.0 opens wide opportunities for anyone to advance. Information that is very abundant provides great benefits for the development of science and the economy. People in the era of the industrial revolution 4.0 have a very large dependence on using information technology. Based on the background that has been explained, the problem can be formulated through the question "How to develop economic-based ecotourism business opportunities in the era of the industrial revolution 4.0? The purpose of this study is to describe the development of ecotourism based on the economy of Patuanan Leuwimunding Village, Majalengka, to be a business opportunity in the era of the industrial revolution 4.0. Whereas the research method in the preparation of this research is qualitative research by exploring and understanding the meaning that is considered to come from social or humanitarian problems, focusing on individual meanings, and translating the complexity of a problem. This type of research was chosen because qualitative research is able to provide descriptive data in the form of written or spoken words from the behavior of the people being observed. Forms of economic-based ecotourism development activities are 1. Building local tourism competitiveness based on natural resource conservation, village / local tourism potential, namely plengkung tourism objects that can be used as fishing activities and other community activities at the location of the object. 2. Introduction and utilization of opportunities in the era of the industrial revolution 4.0 through social media as a marketing and promotion medium. Patuanan Village, which has tourist destination locations, introduces and promotes it through social media, including YouTube, Facebook, and Instagram. The results of ecotourism development activities based on the economy of business opportunities in the era of the industrial revolution 4.0 are 1. Beautifying the tourism object in Plengkung into an object of economic-based ecotourism. 2. Exposing through social media including YouTube. Abstrak Pembangunan ekonomi daerah yang kuat dan berkelanjutan merupakan sebuah kolaborasi yang efektif antara pemanfaatan sumberdaya yang ada, masyarakat dan pemerintah. Salah satu upaya pemanfaatan sumberdaya yang optimal adalah dengan mengembangkan pariwisata dengan konsep Ekowisata. Revolusi industri 4.0 membuka peluang yang luas bagi siapapun untuk maju. Informasi yang sangat melimpah menyediakan manfaat yang besar untuk pengembangan ilmu pengetahuan maupun perekonomian. Masyarakat di era revolusi industri 4.0 memiliki ketergantungan yang sangat besar dalam menggunakan teknologi informasi. Berdasarkan latar belakang yang telah dijelaskan maka dapat dirumuskan masalahnya melalaui pertanyaan ”Bagaimana mengembangkan ekowisata berbasis ekonomi peluang bisnis di era revolusi industri 4.0? Adapun tujuan penelitian ini adalah menggambarkan pengembangan ekowisata berbasis ekonomi Desa Patuanan Leuwimunding Majalengka menjadi peluang bisnis di era revolusi industri 4.0. Sedangkan metode penelitian dalam penyusunan penelitian ini adalah penelitian kualitatif dengan melakukan ekplorasi dan memahami makna yang dianggap berasal dari masalah sosial atau kemanusian, berfokus pada makna individual, dan menerjemahkan komplesitas suatu persoalan. Jenis penelitian ini dipilih karena penelitian kualitatif mampu memberikan data deskriptif berupa kata-kata tertulis atau lisan dari perilaku orang yang diamati. Bentuk kegiatan pengembangan ekowisata berbasis ekonomi adalah 1. Membangun daya saing wisata lokal dengan berbasis konservasi sumber daya alam, potensi wisata desa/lokal yaitu objek wisata situ plengkung dapat dijadikan kegiatan pemancingan dan aktifitas masyarakat lainnya yang di lokasi objek tersebut. 2. Pengenalan dan pemanfaatan peluang di era revolusi industri 4.0 melalui sosial media sebagai media pemasaran dan promosi. Desa Patuanan yang memiliki lokasi tujuan wisata memperkenalkan dan mempromosikan melalui media sosial diantarnya berupa youtube, facebook, instragram. Hasil Kegiatan pengembangan ekowisata berbasis ekonomi peluang bisnis di era revolusi industri 4.0 adalah 1. Mempercantik objek wisata situ plengkung menjadi objek ekowisata berbasis ekonomi. 2. Mengekspos melalui media sosial diantaranya youtube.